ANALISIS PROGRAM REPLANTING KEBUN KELAPA SAWIT ANGGOTA KUD MAKARTI JAYA DI DESA KUMAIN KECAMATAN TANDUN KABUPATEN ROKAN HULU - Risman, Risman; Iskamto, Dedi (Eko dan Bisnis: Riau Economic and Business Review, 2018)
This research was conducted at KUD Makarti Jaya Desa Kumain Kec. Tandun Kab. Rokan Hulu. The formulation of the problem in this research is how the constraints and solutions in the replanting program of oil palm plantation member Karti Makarti Jaya village Kumain Tandun District Rokan Hulu District. The purpose of this research is to know the obstacle constraint which inhibit replanting program and to know the solution of palm oil replanting program of KUD makarti member Jaya Desa Kumain Tandun District Rokan Hulu Regency. The research method using qualitative descriptive method, the researcher use informant or resource as data source, this research can be concluded that the replanting constraint of oil palm plantation in KUD Makarti Jaya Desa Kumain is the debt of Cooperative member to bank and certificate of plot as the benefit, the cost of replanting is big enough. the cost of living of cooperative members during replanting is done until the plant produces (productive) returns, lack of awareness of members in building cooperatives in the future. The solution is to avoid the debt when the oil palm plant near the time of replanting, planting other plants or open new gardens so that farmers' income members uninterrupted during the replanting, intercropping system at the beginning of rejuvenation, between 1-3 years on the land, awareness of cooperative members about the importance of togetherness, please help and participation of members in advancing cooperative organizations